Entorhinal cortex–hippocampal circuit connectivity in health and disease - Hernández-Frausto, Melissa; Vivar, Carmen (Frontiers in Human Neuroscience, 2024)
The entorhinal cortex (EC) and hippocampal (HC) connectivity is the main source of episodic memory formation and consolidation. The entorhinal-hippocampal (EC-HC) connection is classified as canonically glutamatergic and more recently has been characterized as a noncanonical GABAergic connection. Recent evidence shows that both EC and HC receives inputs from dopaminergic, cholinergic, and noradrenergic projections that modulates the mnemonic processes linked to the encoding and consolidation of memories. In the present review, we address the latest findings on the EC-HC connectivity and the role of neuromodulations during the mnemonic mechanisms of encoding and consolidation of memories and highlight the value of cross-species approach to unravel the underlying cellular mechanisms known. Furthermore, we discuss how EC-HC connectivity early neurodegeneration may contribute to the dysfunction of episodic memories observed in aging and Alzheimer's disease (AD). Lastly, we described how exercise may be a fundamental tool to prevent or decrease neurodegeneration.